Un aspecto de la caja negra de RRHH: el rendimiento en los puestos de trabajo (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The problem of the “black box”, in human resources, makes reference to the underlying mechanisms in the positive relation between practices of RRHH and enterprise performance. One of the variables that intermediate this relation is the performance of the personnel. In order to obtain that the human resources reach a high performance it is required to include/understand how one surrenders in a job. In the article sample that the performance is a complex variable, as much with respect to the conducts that explain like a the process by which the same ones are obtained.
Keywords: human performance; resources; black box